MARKETING MARGIN OF CLIMBING PERCH WITH BIOFLOC CULTURE SYSTEM IN BANJARMASIN CITY SOUTH KALIMANTAN - Lilimantik, Emmy (International Journal of Scientific Research and Management (IJSRM), 2020)
This research aims to determine the pattern of marketing channels and marketing margin of climbing perch produced by the biofloc system cultivation in Banjarmasin, South Kalimantan. The sample of the producers was determined using the census method, while the sample of middlemen was determined using the snowball sampling method. The analysis used are (a) analysis of marketing channel patterns and (b) analysis of marketing margins, the data used consists of primary data and secondary data. The results of the analysis show (a) the marketing of climbing perch from the cultivation of the biofloc system consists of two channels and (b) the total amount of marketing margin is 11.300 IDR with details (a) the marketing cost incurred by the middlemen is 2.500 IDR and by the retailers is 2.456 IDR; (b) the profit received by the middlemen is 2.800 IDR and the retailers 3.544 IDR. The profit distribution is bigger than the distribution of the marketing costs, as a result, the profits received by the seller (i.e. middlemen, retailers) are higher than the amount of marketing costs incurred. These conclude that marketing from the side of seller (i.e. middlemen, retailers) is efficient.Keywords: Climbing perch, middlemen, retailers, marketing channels and marketing margins.